Experimental investigation on combustion efficiency of a partially premixed kerosene-air rotating detonation combustor. (1st December 2022) - Xu, Shida; Song, Feilong; Wu, Yun; Zhou, Jianping; Cheng, Peng; Yang, Xingkui; Chen, Xin
Highlights: The kerosene-hot air rotating detonation was successfully realized. The combustion efficiency evaluation method based on mass flow function was proposed. The partial premixing strategy was applied to improve the combustion efficiency. The flashback event was found out under the high premixed equivalence ratio. Abstract: It is believed that detonation waves travel a radially stratified mixture in a non-premixed rotating detonation combustor (RDC), which can result in non-ideal detonations. In order to further improve the combustion performance of RDCs, this paper presents a kerosene-air rotating detonation combustor with a partial premixing strategy, in which part of the fuel is injected into the air plenum to improve the mixing effect. A more convenient and accurate combustion efficiency evaluation method based on the mass flow function (MFF) and equivalent available pressure (EAP) is proposed to help to quantitatively study the combustion performance. A marked improvement in the combustion efficiency and operation range is obtained with increasing premixed equivalence ratio compared to a non-premixed strategy. The highest combustion efficiency for 0.3 premixed equivalence ratio can reach 98.06% in the experiments. The experimental results confirm that this partial mixing strategy can effectively prevent the flashback and improve combustion efficiency within a reasonable equivalence ratio. However, a total equivalence ratio and a premixed equivalence ratio that are too high will lead to a decrease in combustion efficiency and even failed detonation due to flashback events.